Comparative genomics of Bacillus anthracis strains from anthrax outbreaks in Kruger National Park, South Africa - Van Heerden, Henriette (University of Pretoria, 2023)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2022.